Enter a problem...
Algebra Examples
s=2LW+2LH+2WHs=2LW+2LH+2WH
Step 1
Rewrite the equation as 2LW+2LH+2WH=s2LW+2LH+2WH=s.
2LW+2LH+2WH=s2LW+2LH+2WH=s
Step 2
Subtract 2LW2LW from both sides of the equation.
2LH+2WH=s-2LW2LH+2WH=s−2LW
Step 3
Step 3.1
Factor 2H2H out of 2LH2LH.
2H(L)+2WH=s-2LW2H(L)+2WH=s−2LW
Step 3.2
Factor 2H2H out of 2WH2WH.
2H(L)+2H(W)=s-2LW2H(L)+2H(W)=s−2LW
Step 3.3
Factor 2H2H out of 2H(L)+2H(W)2H(L)+2H(W).
2H(L+W)=s-2LW2H(L+W)=s−2LW
2H(L+W)=s-2LW2H(L+W)=s−2LW
Step 4
Step 4.1
Divide each term in 2H(L+W)=s-2LW2H(L+W)=s−2LW by 2(L+W)2(L+W).
2H(L+W)2(L+W)=s2(L+W)+-2LW2(L+W)2H(L+W)2(L+W)=s2(L+W)+−2LW2(L+W)
Step 4.2
Simplify the left side.
Step 4.2.1
Cancel the common factor of 22.
Step 4.2.1.1
Cancel the common factor.
2H(L+W)2(L+W)=s2(L+W)+-2LW2(L+W)
Step 4.2.1.2
Rewrite the expression.
H(L+W)L+W=s2(L+W)+-2LW2(L+W)
H(L+W)L+W=s2(L+W)+-2LW2(L+W)
Step 4.2.2
Cancel the common factor of L+W.
Step 4.2.2.1
Cancel the common factor.
H(L+W)L+W=s2(L+W)+-2LW2(L+W)
Step 4.2.2.2
Divide H by 1.
H=s2(L+W)+-2LW2(L+W)
H=s2(L+W)+-2LW2(L+W)
H=s2(L+W)+-2LW2(L+W)
Step 4.3
Simplify the right side.
Step 4.3.1
Simplify each term.
Step 4.3.1.1
Cancel the common factor of -2 and 2.
Step 4.3.1.1.1
Factor 2 out of -2LW.
H=s2(L+W)+2(-LW)2(L+W)
Step 4.3.1.1.2
Cancel the common factors.
Step 4.3.1.1.2.1
Cancel the common factor.
H=s2(L+W)+2(-LW)2(L+W)
Step 4.3.1.1.2.2
Rewrite the expression.
H=s2(L+W)+-LWL+W
H=s2(L+W)+-LWL+W
H=s2(L+W)+-LWL+W
Step 4.3.1.2
Move the negative in front of the fraction.
H=s2(L+W)-LWL+W
H=s2(L+W)-LWL+W
Step 4.3.2
To write -LWL+W as a fraction with a common denominator, multiply by 22.
H=s2(L+W)-LWL+W⋅22
Step 4.3.3
Write each expression with a common denominator of 2(L+W), by multiplying each by an appropriate factor of 1.
Step 4.3.3.1
Multiply LWL+W by 22.
H=s2(L+W)-LW⋅2(L+W)⋅2
Step 4.3.3.2
Reorder the factors of (L+W)⋅2.
H=s2(L+W)-LW⋅22(L+W)
H=s2(L+W)-LW⋅22(L+W)
Step 4.3.4
Combine the numerators over the common denominator.
H=s-LW⋅22(L+W)
Step 4.3.5
Multiply 2 by -1.
H=s-2LW2(L+W)
H=s-2LW2(L+W)
H=s-2LW2(L+W)